Pengembangan Media Pembelajaran Instalasi Penerangan Listrik menggunakan Mit App Invertor - Rahmadi Eka Putra; Syamsuarnis Syamsuarnis (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
Currently, COVID-19 is hitting Indonesia. This causes disruption of learning activities so that the implementation of learning is direct and transferred online or online. With such circumstances, a solution is needed so that learning and understanding of the material runs effectively and can be accessed anywhere by students one off which is by learning to use learning media with the mit app inverter application. The type of research used in this research is research and development with a 4D model namely define, design, develop, and distribute. The subjects in this study were class XI TITL 1 SMK Negeri 1 West Sumatra students who were in the first semesters of the 2021/2022 academic year. Based on the test in this study, it was found that the validity value of the media assessed by the two validators obtained an average result of 85%w with a valid category. The practicality test based on the results of the teacher questionnaire responses was 81.11%i in the Very Practical category and the results of the question responses from 22 students with an average of 76% categorized as very practical. Int the effective test, the posttest results obtained with an average complete of 86%i in the effective category.